Opioid overdose knowledge among college students in a high overdose death state. Issue 7 (3rd October 2019) - Stover, Amanda N.; Grogg, Kristin; Patel, Jayeshkumar; Thornton, Douglas; Dwibedi, Nilanjana
ABSTRACT: The goal of this study was to investigate university students' knowledge about the identification of opioid overdose and actions to take in an overdose emergency. A cross-sectional, anonymous, 36-item survey was developed and administered to West Virginia University (WVU) students. Overdose knowledge was assessed using the Opioid Overdose Knowledge Scale (OOKS). Demographic information, health insurance coverage status, previously receiving an opioid prescription, and knowledge about West Virginia Good Samaritan laws were also collected. Online survey responses were collected via REDCap. The study sample (n = 214) was 90% white, 72.5% female, had a mean age of 24.8 years, and over half previously received a prescription opioid (51.9%). Additionally, 6.5% reported witnessing an overdose in the past year, and 15.9% previously received naloxone training. Overall, our participants had an average score of 30.9 out of 45 on the OOKS. Participants who previously received naloxone training scored higher overall on the OOKS than participants who did not ( p < .001). Similarly, participants who previously received a prescription for an opioid also scored higher than participants who had never had a previous prescription for an opioid ( p < .001). University students' knowledge suggests that previous exposure to opioid prescriptions and naloxone training increase a student's knowledge about opioid overdose. This information is not surprising; however, this does make the case that students may benefit from brief overdose education programs that could be implemented across university health education curricula. However, a larger effort may need to be implemented to encourage students to participate in such programs.